Students’ perceptions towards bullying in mission schools, Kuching, Sarawak / Audrey Letan - Letan, Audrey (2017)
The purpose of the study is to identify bullying behavior among the students in mission schools in Kuching, Sarawak. The study attempts to identify the reason of bullying, the location of bullying, ways to discourage bullying, the prevalence of verbal and physical bullying and school safety issues based on the students’ perceptions. The study adopted descriptive survey design. A total 235 students from four mission schools in Kuching city participated in this study. The information gathered is from Peer Relations Questionnaire - PRQ and The Nature and Prevalence of Bullying in Schools Questionnaire. The alpha Cronbach for the instrument are .788. Results shown that bullying was perceived differently by the students in respective schools. Students reported that the overall rate of the bullying prevalence were at moderate level. There is no significant difference on the prevalence of bullying between male and female students but there is a significant difference on the prevalence between verbal bullying and physical bullying. According the results, the students perceived that they are capable to response to the bullying behavior and that the students agreed that both teachers and students must cooperate to stop bullying in schools. The result also indicated that the students perceived bullying is the most serious issue in school.